An update of morphological and distributional data of the genus Patrera Simon (Araneae: Anyphaenidae: Anyphaeninae) with the description of twenty-five new species from Colombia - Martínez, Leonel; Brescovit, Antonio D.; Villarreal, Eduardo; Oliveira, Luiz Fernando M. (Zootaxa, 2021)
The knowledge on the diversity of the genus Patrera Simon in Colombia is widely expanded. P. auricoma (L. Koch, 1866) and P. armata (Chickering, 1940) are redescribed and their females are described for the first time and recorded from Cundinamarca and Meta departments, respectively. Aysha strandi (Caporiacco, 1947) is synonymized with P. armata. Three species groups in the genus Patrera are proposed to include the bulk of its species (fulvastra, florezi, and philipi). These groups are diagnosed based on sexual characters. Twenty-five new species are herein described, illustrated and mapped: P. anchicaya n. sp. (♂♀); P. barbacoas n. sp. (♂); P. borjai n. sp. (♂♀); P. danielae n. sp. (♂♀); P. dimar n. sp. (♂♀); P. perafani n. sp. (♂♀); P. platnicki n. sp. (♂); P. quillacinga n. sp. (♂♀), and P. ramirezi n. sp. (♂♀) into the fulvastra species group. P. bonaldoi n. sp. (♂♀); P. boteroi n. sp. (♂); P. carvalhoi n. sp. (♂♀); P. florezi n. sp. (♂♀); P. perijaensis n. sp. (♀); P. quimbaya n. sp. (♂♀); P. sampedroi n. sp. (♂); P. yukpa n. sp. (♂♀), and P. wiwa n. sp. (♂♀) in florezi species group. P. sutu n. sp. (♂); P. chucurui n. sp. (♂♀); P. dawkinsi n. sp. (♂); P. dentata n. sp. (♂); P. dracula n. sp. (♂); P. kuryi n. sp. (♂♀), and P. longitibialis n. sp. (♂) in philipi species group. We also briefly discuss some aspects of the species groups’ genital morphology, based on a comparison with the type, P. fulvastra Simon. Additionally, distribution maps for all Colombian species including new records for P. armata (Chickering, 1940), P. auricoma (L. Koch, 1866) and P. suni Dupérré & Tapia, 2016 from Cundinamarca, Meta and Nariño departments are also herein included.